Observations of an atmospheric gravity wave by shear instability in katabatic wind at Mizuho Station, East Antarctica - Kobayashi, Shun'ichi; Ishikawa, Nobuyoshi; Ohata, Tetsuo; Kawaguchi, Sadao (1982)
P(論文) Measurements were made of vertical wind speed components, using two sonic anemothermometers on the snow surface at Mizuho Station in 1980 by the present authors who were members of the 21st Japanese Antarctic Research Expedition (JARE-21). The two anemothermometers were mounted at the fixed heights of 3m and 30m on a 30-m-high micrometeorological tower. The existence of shear instability (Kelvin-Helmholtz) waves with period of about 20s was revealed as a result. The maximum aplitude of the K-H waves was found when the surface layer had a local gradient Richardson number smaller than 0.25; the instability regime was in agreement with DRAZIN's criterion (J. Fluid. Mech., 4,214,1958). Such gravity waves were observed when a strong surface inversion was progressing above the snow surface after the katabatic wind had been disturbed by a synoptic scale disturbance. departmental bulletin paper